Why Focus on Spending Needs Factors? : The Political Economy of Fiscal Transfer Reforms in Mexico - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 2007)
An equalization system ensures that subnational governments can provide similar level of public services at a comparable level of own tax-effort. This paper focuses on the importance of spending needs factors in the design of equalization transfers as well as special purpose transfers-and the role that this could have in setting the agenda for better accountability for recipient governments, illustrating both design and implementation questions with examples from Mexico. The paper also takes into account the difficult political economy constraints to reforming any system of transfers.